Response to ruxolitinib in patients with intermediate‐1–, intermediate‐2–, and high‐risk myelofibrosis: results of the UK ROBUST Trial. (30th March 2015) - Mead, Adam J.; Milojkovic, Dragana; Knapper, Steven; Garg, Mamta; Chacko, Joseph; Farquharson, Mira; Yin, John; Ali, Sahra; Clark, Richard E.; Andrews, Chris; Dawson, Meryem Ktiouet; Harrison, Claire
Summary Myelofibrosis is characterized by splenomegaly and debilitating constitutional symptoms that negatively impact patients' quality of life. ROBUST, a UK, open‐label, phase II study, evaluated the safety and efficacy of ruxolitinib in patients with myelofibrosis (N = 48), including intermediate‐1 risk patients. The primary composite endpoint was the proportion of patients achieving treatment success [≥50% reduction in palpable spleen length and/or a ≥50% decrease in Myelofibrosis Symptom Assessment Form Total Symptom Score (MF‐SAF TSS)] at 48 weeks. This was the first time that efficacy of ruxolitinib in myelofibrosis has been evaluated based on these criteria and the first time the MF‐SAF was used in a population of patients solely from the United Kingdom. Overall, 50% of patients and 57% of intermediate‐1 risk patients, achieved treatment success; reductions in spleen length and symptoms were observed in all risk groups. The majority of patients (66·7%) experienced ≥50% reductions from baseline in spleen length at any time. Improvements in MF‐SAF TSS were seen in 80·0%, 72·7%, and 72·2% of intermediate‐1, intermediate‐2, and high‐risk patients, respectively. Consistent with other studies of ruxolitinib, the most common haematological adverse events were anaemia and thrombocytopenia. Results indicate that most patients with myelofibrosis, including intermediate‐1 risk patients, may benefit from ruxolitinib treatment.